A 10-base-pair element of the human immunodeficiency virus type 1 long terminal repeat (LTR) is an absolute requirement for transactivation by the human cytomegalovirus 72-kilodalton IE1 protein but can be compensated for by other LTR regions in transactivation by the 80-kilodalton IE2 protein. - Walker, S (1992)
Transient gene expression studies have indicated that human cytomegalovirus (HCMV) specifically transactivates the human immunodeficiency virus (HIV) long terminal repeat (LTR). We show here, by a specific mutational analysis, that only the TATA box region is obligatory for transactivation of the HIV-1 LTR by HCMV. Similarly, this element is also sufficient for transactivation by either the HCMV 72-kDa major immediate-early 1 (IE1) or 80-kDa IE2 gene product independently. However, deletion of a 10-bp region from the minimal responsive element, 5' to the TATA box, dramatically reduced the level of HCMV 72-kDa IE1 or 80-kDa IE2 transactivation, indicating a crucial role for this element in transactivation. Whereas inclusion of the TAR element or Sp1 sites on this 10-bp-deleted minimal promoter had no effect on the removal of IE1 transactivation, TAR and Sp1 elements did compensate for the 10-bp element in transactivation by IE2 and HCMV. Consequently, the sequence requirements of the HIV-1 LTR for transactivation by HCMV can be reproduced by these IE1 and IE2 gene products of HCMV.